Dendrobium zhenyuanense (Orchidaceae), a new Chinese species in section Stachyobium - Li, Jian-Wu; Ye, De-Ping; Jin, Xiao-Hua; Yin, Jian-Tao (Phytotaxa, 2014)
Dendrobium Swartz (1799: 82) comprises approximately 1500 species and is one of the largest genera of Orchidaceae. It is widespread in tropical and subtropical regions of Asia and Australia, from India to Japan, south to Malaysia and Indonesia, east to Australia, New Guinea and the Pacific islands (Cribb & Govaerts, 2005; Wood 2006; Zhu et al. 2009). Recently, there have been debates about the generic delimitation of Dendrobium (Kraenzlin 1910, Schlechter 1911–1914, Tang & Wang 1951, Brieger 1981, Seidenfaden 1985, Yukawa et al. 2000, Clements & Jones 2002, Clements 2003, Wood 2006, Burke et al. 2008, Adams 2011, Schuiteman 2011, Xiang et al. 2013). Here we follow the broad concept of Dendrobium. There are about 80 species in China, of which 14 species are endemic (Chen, 2009).